2020
DOI: 10.21608/edj.2020.79132
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antimicrobial activity of manually agitate (nano- chitosan and nano- propolis) against Enterococcus faecalis in comparison with sodium hypochlorite: an in-vitro study

Abstract: Aim:The purpose of this study was to evaluate in an in-vitro model the antibacterial efficacy of manually agitated nano-chitosan and nano-propolis as root canal irrigation protocols in comparison to manually agitated sodium hypochlorite against Enterococcus Faecalis. Material and Methods:The root canals of 50 single rooted human premolars were flattened to a standard length of 18mm cleaned and shaped to a size F5 Protaper, apices closed with composite, fixed into an Eppendorf vial with silicon impression mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…These results agreed with the findings of Perochena et al [36] who showed that CNPs solution was significantly better than NaOCl and contradicted those of Roshdy et al [22] and Moukarab [37] who found no significant difference between CNPs and NaOCl. The difference in findings could be attributed to the different circumstances, where they tested the solutions in vitro against E. faecalis biofilm while the current study tested them clinically against the multispecies primary endodontic infection.…”
Section: Table 2: the Median And Range Values Of Post-operative Anaerobic And Aerobic Bacterial Count In The Four Groupssupporting
confidence: 89%
“…These results agreed with the findings of Perochena et al [36] who showed that CNPs solution was significantly better than NaOCl and contradicted those of Roshdy et al [22] and Moukarab [37] who found no significant difference between CNPs and NaOCl. The difference in findings could be attributed to the different circumstances, where they tested the solutions in vitro against E. faecalis biofilm while the current study tested them clinically against the multispecies primary endodontic infection.…”
Section: Table 2: the Median And Range Values Of Post-operative Anaerobic And Aerobic Bacterial Count In The Four Groupssupporting
confidence: 89%
“…Arachidonic acid's lipoxygenase pathway is inhibited by flavonoids. As a result, they play a crucial role in lowering the inflammatory response (27) . Flavonoids are topoisomerase inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that propolis can break the bacterial resistance produced by certain bacterial strains as E faecalis and S aureus. It was also reported that ethanolic propolis extract induced dentin bridge formation and bone regeneration when propolis comes in contact with exposed pulpal tissues (15) .…”
Section: Introductionmentioning
confidence: 97%
“…In the field of endodontics chitosan tested to replace EDTA as final irrigating solution, it has chelation ability comparable to that of EDTA which perfectly removes the smear layer through dissolving its inorganic components. Moreover, chitosan has an advantage over EDTA of possessing antimicrobial impact against broad range of microorganisms and that are isolated from root canal infection as Enterococcus faecalis and Candida albicans had been demonstrated (9,10) .…”
Section: Introductionmentioning
confidence: 99%